Effect of irrigation and inoculation on growth and yield of wheat (Triticum aestivum) and lentil (Lens culinaris) grown pure and in intercropping systems - GHOSH, AMAL; PUSTE, A M (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1990-91 and 1991-92 to study the performance of wheat (Triticum aestivum L. emend. Fiori & Paol.) and lentil (Lens culinaris Medik.) after pre-sowing seed inoculation with N-fixing bacteria (Azotobacter lipoferum Beijerinck, comb. nov. and Rhizobium leguminosarum Rank respectrively) grown pure and in intercropping systems under different levels of irrigation scheduled at critical growth stages of wheat. Result showed higher grain yield (3.40 tonnes/ha) due to 4 irrigations for wheat and 2 irrigations for lentil (1.16 tonnes/ ha). The seed inoculation before sowing recorded 7.04-9.37% more yield of wheat and 64.28-65.35% of lentil compared with the uninoculated control. The inoculated pure crop out yielded the mixed one. However, grain yield due to wheat intercropped with lentil in 5 : 3 ratio was superior to that in 4 : 2 ratio.